Surveillance of Naegleria fowleri in Louisiana's public water systems - Lauren Ward; Samendra P. Sherchan (IWA Publishing, 2023)
The free-living amoeba Naegleria fowleri (Nf) inhabits soil and natural waters worldwide: it is thermophilic and thrives at temperatures up to 45 °C and in a multitude of environments. Three deaths in Louisiana were attributed to primary amoebic meningoencephalitis (PAM) caused by Nf infection in 2011 and 2013. Following these incidents, public water systems are now monitored for the presence of Nf in Louisiana. From 2014 to 2018, 29% (27/93) of samples collected showed positive for Nf and 68% (63/93) showed all thermophilic amoeba culture. Ten raw water sources and 17 distribution water systems tested positive. The year 2017 showed the highest number of samples with Nf (n = 10) followed by nine samples in 2015. As climate change increases surface water temperatures, continued testing for Nf prevalence will be an important facet of water monitoring and will need to extend into locations farther north than the current most common range. HIGHLIGHTS The occurrence of Naegleria fowleri in public water systems was studied.; About 29% (27/93) of samples collected showed positive for Nf.; More research is warranted to determine the survival of this emerging pathogen in water systems.;